Absorption of Calcium Administered Alone or in Fixed Combination with Vitamin D to Healthy Volunteers - Scotti, Aurelio; Bianchini, Carlo; Abbiati, Gianalfredo; Marzo, Antonio (Arzneimittelforschung, 2001)
Calcium supplementation is widely used in deficiency status and as an adjuvant in the treatment of osteoporosis.As usual with endogenous substances, the calcium absorption, distribution and elimination processes are strictly controlled by homeostatic equilibria. Free calcium ion is the most representative active fraction of the circulating ion. Ion excretion is controlled by a saturable tubular reabsorption process which leads to a renal threshold. Cumulative urinary excretion of calcium is the end-point of absorption, distribution and elimination processes, and is thus a good indicator of bioavailability.In order to increase the oral bioavailability of calcium, the ion is administered in association with vitamin D, which is known to enhance intestinal calcium absorption.The aim of this study was to evaluate the absorption of calcium administered alone and in fixed combination with cholecalciferol (vitamin D3, CAS 67-97-0). In accordance with the study protocol, calcium carbonate (CAS 471-34-1; 1500 mg = 600 mg as calcium ion) was administered as such (reference) and associated with cholecalciferol (400 IU) (test) for four days (2 doses/day) to 18 healthy male volunteers in a sequential pattern, namely reference followed by test.Urinary excretion of total calcium, and serum concentration of free and total calcium, 25-OH-vitamin D3 and parathyroid hormone were carefully analysed the day before (baseline) and on the 4th day of dosing, with validated methods.The effect of cholecalciferol in promoting calcium absorption was clearly observed from urinary excretion of total calcium, which with the test treatment showed a 16.6 % increase in excretion (p=0.025) compared with the reference treatment. The mean excretion values on the 4th day, expressed in mg, were 238.85 and 204.83 with test and reference respectively.Moreover, the results demonstrated an increased serum concentration of both free and total calcium after dosing with test and reference by comparison with the baseline situation. The area under the serum concentration-time curve of total calcium increased from day -1 to day 4 from 550.98 to 575.90 mgl−1 h with test and from 543.03 to 568.16 mgl−1 h with reference. Similarly, ionised calcium increased on day 4 with both the treatments.Parathyroid hormone showed the expected typical decreasing behaviour after dosing with the test and reference drugs.The results of this study suggest that calcium carbonate is absorbed through the intestine when administered either alone or in association with cholecalciferol. Cholecalciferol, however, showed the typical expected activity in promoting calcium absorption, which was evident from the cumulative urinary excretion of the ion.To the authors’ knowledge, this study is the first published paper demonstrating the absorption and pharmacodynamic effect of short-term administration of vitamin D associated with calcium at the doses recommended for supplementation in a fixed-combination pharmaceutical product.
Keywords: Calcium, absorption, bioavailability, combination with vitamin D; CAS 67-97-0; CAS 471-34-1; Cholecalciferol, combination with calcium; Natecal D3®; Vitamin D